The role of a tire in vehicle and road interaction - Rutka, Arūnas; Sapragonas, Jonas (Transport, 2002)
Major difficulties in road surface description lies in the evaluation of the tire and road interaction. Main purpose of this paper is to analyse the influence of the tire in vehicle and road interaction with the purpose to choose more commons, but enough precise tire models. Data of profile used in investigations were measured in real roads. For the investigation of the tire’s smoothing function two models were used: flexible narrow ring-2D estimates the tire and road contact in a line and flexible band-3D estimates dimensional contact between the road and tire. Results of computations are presented in figures. There were determinate that tire does not fully smooth irregularity of surface texture level. First Published Online: 19 Oct 2011